Utilization of Multimedia Facilities and Internet Media as Effective Learning Tools - Irika Widiasanti; Noval Anki Ramadhan; Muhammad Alfarizi; Aisyah Nur Fairus; Astrid Wardani Oktafiani; Dhiya Thahur (Jurnal Penelitian Pendidikan IPA, 2023)
Utilization of multimedia facilities and internet media in the learning process has a significant advantage. Learning that uses multimedia technology and internet media can increase student effectiveness, creativity, and motivation. Although, this requires management and presentation of material according to the needs and characteristics of students. This study aims to determine the use of multimedia and internet media as effective learning tools. In writing this article, the researcher uses a qualitative method of literature study, namely searching for documents, articles, and previous research to examine references and research results related to the use of multimedia and internet technology in learning. The results of the study show that multimedia and internet technology can be effective learning tools with more interactive and interesting learning experiences. This increases students' motivation and interest in learning, thereby helping to create a more creative and innovative learning environment. In conclusion, the use of multimedia and internet technology in learning can improve the quality of learning and provide a more positive learning experience for students. Therefore, it is necessary to pay more attention to the management and presentation of appropriate material so that multimedia and internet technology can become effective learning tools